Web-based Information Systems and Knowledge Management's Impact on Worker Performance - Ambo'Miri, Sitti Wan Fazirah binti; Kusuma, Bayu Wijaya; Halimah, Asih Nur (Pandawan Sejahtera Indonesia, 2023)
The process of doing a literature review involves learning about and examining the findings of research that has been published by researchers in relation to earlier bodies of knowledge. Activities that involve reviewing the literature might improve knowledge-building in relation to ongoing research. with the investigation being made. Making an effective and accurate literature review requires using relevant research and the findings of prior studies. study findings The findings of earlier studies and pertinent research are helpful in bolstering theories, notions, and phenomena connected to and influencing the generation of variables. the development of variables through connected and influencing processes. The performance of a company's employees is reviewed in this article in detail company. These elements include knowledge management, web-based information systems, and literature reviews. The Executive Support System (ESS) for Business is the subject of an information system, knowledge management, and literature review. The effects of web-based information systems on employee performance and knowledge management on employee performance are just a few of the outcomes that can be gained via literature research efforts